Pemahaman Program Bandar Selamat dalam Keselamatan Awam (Jenayah) di Wangsa Maju Kuala Lumpur (Jurnal Pembangunan Sosial, 2013)
In recent years crime and safety issues are among the key issues that have attracted public attention in Malaysia. It is undeniable that the issue of crime is closely related to the implementation of the Safe City Program which was established in 2004 to improve public safety of the community. This program is an effort made by the Government of Malaysia to overcome the rise in crime rates. This study further explores the public perception towards the Safe City Program implemented in their housing area. The objectives of this study are to identify the level of security in housing areas, to identify the fear of crime among the population in that area and to identify crime prevention measures under the Safe City Program that are most suitable for implementation in the area from the perception of the local population. The selected study area is Taman Perumahan Wangsa Melawati, Wangsa Maju, Kuala Lumpur. The results showed that most of the respondents are not certain about the level of security in their residential area. In terms of fear of crime, the study found that the residents feel safe living in this area. Meanwhile, from the respondents’point of view, the most suitable crime prevention measures to be implemented in this area are the provision of police posts or mobile stations, improved surveillance in the residential area and the installation of CCTVs in commercial premises and public places. In order to improve the Safe City Program in this area, it is recomended that the residents activate the Resident’s Association, and the Kuala Lumpur City Hall enhances its role in the security aspect under its jurisdiction.